Effects of Different Durations of 9-Square Dance Exercise Versus Treadmill Exercise on the Physical Fitness and Quality of Life of Healthy Volunteers: A Pilot Randomized Controlled Trial - Puttipaibool S. (2023)
Objective: To evaluate the impact of 9-square dance exercise (9SDE) on physical fitness and quality of life compared to traditional treadmill exercise (TME). Materials and Methods: In total, 33 healthy volunteers (10 men, 23 women) were recruited and randomly assigned into three groups: 9 square dance exercise for 8 minutes (9SDE-8), 9 square dance exercise for 30 minutes (9SDE-30), or treadmill exercise (TME). Exercises were done three times a week for 12 weeks and physical fitness tests were performed for all the groups at weeks 0, 6, and 12. Participants were assessed using the European Quality of Life Measure 5 Domains and 5 Levels questionnaire (EQ-5D-5L). Results: Significant improvements in cardiorespiratory endurance, leg strength, and flexibility were demonstrated in the 9SDE-30 group (p<0.05). There was no significant difference in physical fitness between the 9SDE-30 and TME groups. The 9SDE-8 group showed a significant improvement in utility in the EQ-5D-5L questionnaire (p<0.05), while the TME group showed a significant improvement in directly evaluated health status (p<0.05). 9SDE-30 and TME showed similar improvements in cardiorespiratory endurance and leg strength. Conclusion: Considering its low-resource requirement and overall utility, coupled with its effectiveness in promoting cardiovascular fitness and leg strength, 9SDE represents a viable exercise alternative for those with limited time and resources.